Early Stage Risk Identification and Governance of Major Emerging Infectious Diseases: A Double-Case Study Based on the Chinese Context - Li X; Jiang H; Liang X (Dove Medical Press, 2023)
Xuefeng Li,1,2 Hui Jiang,1 Xiaoyu Liang1 1School of Engineering Science, University of Chinese Academy of Sciences, Beijing, 100049, People's Republic of China; 2School of Public Policy and Management, University of Chinese Academy of Sciences, Beijing, 100049, People's Republic of ChinaCorrespondence: Hui Jiang, School of Engineering Science, University of Chinese Academy of Sciences, 19 Yuquan Road, Shijingshan District, Beijing, People's Republic of China, Email huijiang@ucas.ac.cnPurpose: Based on the Chinese context, this study uses severe acute respiratory syndrome (SARS) and coronavirus disease 2019 (COVID-19) outbreaks as examples to identify the risk factors that lead to the major emerging infectious diseases outbreak, and put forward risk governance strategies to improve China's biosecurity risk prevention and control capabilities.Material and Methods: This study combines grounded theory and WSR methodology, and utilizes the NVivo 12.0 qualitative analysis software to identify the risk factors that led to the major emerging infectious diseases outbreak. The research data was sourced from 168 publicly available official documents, which are highly authoritative and reliable.Results: This study identified 10 categories of Wuli risk factors, 6 categories of logical Shili risk factors, and 8 categories of human Renli risk factors that contributed to the outbreak of major emerging infectious diseases. These risk factors were distributed across the early stages of the outbreak, and have different mechanisms of action at the macro and micro levels.Conclusion: This study identified the risk factors that lead to the outbreak of major emerging infectious disease, and discovered the mechanism of the outbreak at the macro and micro levels. At the macro level, Wuli risk factors are the forefront antecedents that lead to the outbreak of the crisis, Renli factors are the intermediate regulatory factors, and Shili risk factors are the back-end posterior factors. At the micro level, there are risk coupling, risk superposition, and risk resonance interactions among various risk factors, leading to the outbreak of the crisis. Based on these interactive relationships, this study proposes risk governance strategies that are helpful for policymakers in dealing with similar crises in the future.Keywords: major emerging infectious diseases, risk factors, SARS, COVID-19, grounded theory, WSR methodology